1996
DOI: 10.1063/1.472548
|View full text |Cite
|
Sign up to set email alerts
|

Condensation of supersaturated vapors of hydrogen bonding molecules: Ethylene glycol, propylene glycol, trimethylene glycol, and glycerol

Abstract: The critical supersaturations required for the homogeneous nucleation ͑rate of 1 drop cm Ϫ3 s Ϫ1 ͒ of ethylene glycol, propylene glycol, trimethylene glycol and glycerol vapors have been measured over wide temperature ranges ͑e.g., 280-400 K͒ using an upward thermal diffusion cloud chamber. At lower temperatures the experimental nucleation rates are much higher than the predictions of the classical nucleation theory. Glycerol shows the best agreement between experiment and theory in the temperature range of 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 73 publications
4
36
0
1
Order By: Relevance
“…Heist et al 4 reported a strong increase of the critical supersaturation of n-propanol with pressure for helium and hydrogen, implying a dramatic decrease of nucleation rate with pressure. Kane and El-Shall, 5 also using a TDCC, confirmed this observation for the glycerol-helium system. It has recently become clear, however, that the range of conditions for reliable TDCC operation itself depends on total pressure.…”
Section: Introductionmentioning
confidence: 53%
“…Heist et al 4 reported a strong increase of the critical supersaturation of n-propanol with pressure for helium and hydrogen, implying a dramatic decrease of nucleation rate with pressure. Kane and El-Shall, 5 also using a TDCC, confirmed this observation for the glycerol-helium system. It has recently become clear, however, that the range of conditions for reliable TDCC operation itself depends on total pressure.…”
Section: Introductionmentioning
confidence: 53%
“…In diffusion cloudchamber experiments, [1][2][3][4][5] for example, marked effects of carrier-gas pressure on the rate of nucleation and the critical supersaturation were seen. For a water/nitrogen system, however, a recent experiment 6 using a high pressure pulseexpansion wave tube demonstrated that when the nucleation rate is plotted as a function of conventional supersaturation ͑i.e., the ratio of the partial vapor pressure of the supersaturated vapor to the equilibrium vapor pressure of the pure component͒, the carrier-gas pressure effect is hardly discernible.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of carrier gas particles in the simulation is to mimic real experiments of nucleation [15][16][17][18] where the carrier gas plays a major role in releasing the latent heat generated from nuclei formation. The interaction potential of target-target is a Lennard-Jones ͑LJ͒ type, i.e., a͒ Author to whom correspondence should be addressed.…”
Section: A Molecular Dynamics Simulationmentioning
confidence: 99%